Supporting an integrated transportation infrastructure and public space design: A coupled simulation method for evaluating traffic pollution and microclimate. (January 2020) - Yang, Liu; Zhang, Lufeng; Stettler, Marc E.J.; Sukitpaneenit, Manlika; Xiao, Dunhui; van Dam, Koen H.
Highlights: A multiscale simulation method and an urban modeling-design framework are presented for analyzing and evaluating transport infrastructure and public space urban designs. A mesoscale agent-based model, traffic emission models, and microclimate simulations are coupled to develop the simulation method. A two-fold evaluation is conducted in a case study in Beijing, including mesoscale traffic-related emissions and the resulting air pollution at pedestrian level, in line with the microclimate of public open spaces and thermal comfort. A holistic urban design strategy is helpful for achieving both an integration within the transport infrastructure and public space system and an external integration with the ecosystem. The findings are valuable for supporting urban designers and planners to build an environmentally- and pedestrian- friendly integrated transport infrastructure and public space plan. Abstract: Traditional urban and transport infrastructure planning that emphasized motorized transport has fractured public space systems and worsened environmental quality, leading to a decrease in active travel. A novel multiscale simulation method for supporting an integrated transportation infrastructure and public space design is presented in this paper. This method couples a mesoscale agent-based traffic prediction model, traffic-related emission calculation, microclimate simulations, and human thermal comfort assessment. In addition, the effects of five urban design strategies on traffic pollution and pedestrian level microclimate are evaluated (i.e., a "two-fold" evaluation). A case study in Beijing, China, is presented utilizing the proposed urban modeling-design framework to support the assessment of a series of transport infrastructure and public space scenarios, including the Baseline scenario, a System-Internal Integration scenario, and two External Integration scenarios. The results indicate that the most effective way of achieving an environmentally- and pedestrian- friendly urban design is to concentrate on both the integration of transport infrastructure and public space to mitigate system externalities (e.g., air pollution and heat exhaustion). It also demonstrates that the integrated blue-green approach is a promising way of improving local air quality, micro-climatic conditions, and human comfort.